Two mirrors of power - Norkus, Zenonas (Politologija, 1998)
Basing on the work of Robert Dahl, Keith Dowding, Peter Morriss et al., two methodical approaches in the empirical research on social power are compared: the decisional one and the resource-based one. The article includes the concise presentation of the approaches to the measurement of the voting power and discusses the conceptual pitfalls in the analysis of power. The use of the decisional approach is prone to the commitment of the "exercise fallacy," consisting in the identification of power with its observable manifestations. As a result, the decisional approach confronts the "problem of satellite" and that of "chameleon," which cannot be solved in the framework of the decisional approach. The decisional approach is recommended by the behavioralist philosophy of social research, favoring the social research without theoretical preconceptions. Such preconceptions are unavoidable in the framework of the resource-based approach because the specification and assessment of the relative importance of the resources of social power draw upon some general macrosociological outlook. According to P. Morriss, the "vehicle fallacy" (identification of the disposition with its base) is imminent for the resource-based approach. P. Morriss' diagnosis is specified in the article by the thesis that this fallacy presents real danger only for the interpretation of dispositions of agencies. The author conceives power as an ability of an agency irreducible neither to its basis (resources) nor to its manifestations and reflected only partially by both of its mirrors because of the strategic dimension involved in the use of power. This dimension is explained, drawing upon the work of Herbert Simon on imperfect rationality, the distinction between power and luck made by Brian Barry, and the suggestions of K. Dowding about the impact of the situations of the Prisoner's Dilemma type on the exercise of power. The agency having the power can choose not to exercise it because of (1) its assessment of the situation as lacking the chances of success, (2) being lucky not to be in need to exercise its power because its interests are realized by some other agency, or (3) choosing to free-ride in the situation where the result of the exercise of its power has the features of the public good.
Keywords: -